The mystery genre in English poetry: historical roots and literary evolution - Qurbonov, Parda; Khamrokulov, Behzod (The Lingua Spectrum, 2025)
This article analyzes the formation and development of the mystery genre in English poetry. It examines the unique poetic structure of the genre, its symbolic and allegorical meanings, as well as its place in various literary periods – the Middle Ages, the Renaissance, Romanticism, and Modernism. Mystery poetry is interpreted as a complex artistic system closely connected with religious belief, spiritual values, and the philosophical quests of human thought. The main purpose of this genre is to express the spiritual and existential experiences of humanity in poetic form and to reveal the inner harmony between man and the universe through hidden truths. The article also explores the aesthetic functions of the mystery genre in art and literature, as well as its role in contemporary thought.